Preparation method of rapidly-cured expanded graphite-based fuel cell composite bipolar plate

By using a "sandwich" sandwich structure with soft cut carbon fiber foam and fast curing resin in the preparation of fuel cell composite bipolar plates, the problems of long curing time and uneven performance in the prior art are solved, and efficient and coordinated bipolar plate performance and rapid production are achieved.

CN119526670AActive Publication Date: 2025-02-28SHANGHAI ZHONGCAI ENG DETECTION CO LTD +1

Patent Information

Application Number
CN202411787339.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing preparation methods for fuel cell composite bipolar plates have problems such as long curing time, uneven conductivity and thermal conductivity, insufficient dimensional accuracy and mechanical strength.

Method used

Soft-cut carbon fiber foam and fast-curing resin are used as intermediate media to quickly cure epoxy resin through a "sandwich" sandwich structure and high-temperature rapid curing of epoxy resin to coordinate the conductivity, mechanical strength and airtightness of the bipolar plate.

Benefits of technology

It achieves rapid curing, shortens the production cycle, improves the dimensional accuracy and production efficiency of the bipolar plate, coordinates the conductivity, bending strength and airtightness, and meets the requirements of large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a rapidly-cured expanded graphite-based fuel cell composite bipolar plate, which comprises the following steps: cutting soft cut carbon fiber foam with a three-dimensional structure into the size of the bipolar plate, immersing into liquid resin for 10-30 minutes, and drying in a vacuum drying oven at 25-40 DEG C; and putting the pre-cold-pressed expanded graphite as a top layer and a bottom layer of the bipolar plate into a mold under the pressure of 10-15 Mpa, putting the soft cut carbon fiber foam resin into a middle layer, heating to 90-150 DEG C under the pressure of 10-15 Mpa, keeping for 110 seconds to 58 minutes, and demolding to obtain the composite bipolar plate of the fuel cell. The hot press molding method is simple, the plane conductivity of the prepared bipolar plate reaches 375.8 S / cm, the maximum bending pressure reaches 88.53 N, the bending strength is 61 Mpa, the air tightness is 2.32 * 10 <-8 > cm < 3 > cm < 2 > s <-1 >, the water contact angle is 92 degrees, the corrosion-resistant current is 0.345 mu A / cm < 2 >, and large-scale production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a method for preparing a fast-curing expanded graphite-based fuel cell composite bipolar plate. Background Art

[0002] As a key component of the fuel cell stack, the fuel cell bipolar plate is responsible for distributing reaction gases, collecting current, transferring heat and providing mechanical support. First of all, the composite bipolar plate needs to have excellent electrical conductivity and thermal conductivity to ensure the efficient electrochemical reaction and the timely dissipation of reaction heat. Secondly, the composite bipolar plate needs to have good corrosion resistance and mechanical strength to remain stable in the harsh working environment of the fuel cell. In addition, the composite bipolar plate also needs to have excellent gas sealing to prevent the mixing and leakage of the reaction gases.

[0003] Expanded graphite has good electrical and thermal conductivity and is one of the ideal substrates for preparing fuel cell bipolar plates. At present, the preparation method of expanded graphite-based composite bipolar plates is: the graphite material and resin are mixed and solidified by dry / wet method, and then molded. In order to obtain higher bending strength and air tightness, the selected resin is liquid resin, which usually needs to add curing agent and accelerator, resulting in a long curing time. The shrinkage deformation of the graphite and liquid resin composite material during the long curing of 2-4 hours affects the dimensional accuracy, surface quality, mechanical strength and service life of the bipolar plate; the density and particle size of graphite and resin are different, and the long curing time leads to uneven dispersion of graphite in the resin, which affects the electrical and thermal conductivity of the bipolar plate.

[0004] The patent with publication number CN116995259A, entitled A fuel cell composite bipolar plate and its preparation method, comprises the following steps: activating melamine foam, preparing a nickel plating solution of 0.3-6% nickel chloride, 0.2-4% sodium citrate, 0.5-10% ammonia water and 80-95% deionized water, nickel plating the activated melamine foam, evenly laying graphite material in a mold, pre-pressing for the first time at 1-10 MPa to obtain a bottom graphite plate, laying nickel-plated melamine foam on the bottom graphite plate, evenly laying graphite material on the upper surface, cold-pressing and placing in a vacuum impregnation tank, evacuating and maintaining for 0.5-2 hours, then sucking in a thermosetting resin and pressurizing at 0.01-0.5 MPa for impregnation for 1-20 hours, and curing in an oven at 100-180°C for 1-5 hours to obtain a composite bipolar plate. This method requires that the melamine foam be electroplated, which is a complex process, and then the thermosetting resin is absorbed and pressurized to 0.01-0.5 MPa, immersed for 1-20 hours, and cured in an oven at 100-180°C for 1-5 hours. The long curing time affects the electrical conductivity, thermal conductivity, dimensional accuracy, surface quality, mechanical strength and service life of the bipolar plate. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and provide a method for preparing a fast-curing expanded graphite-based fuel cell composite bipolar plate, which has a simple preparation method, shortens the production cycle through rapid curing, coordinates the conductivity and mechanical strength of the composite bipolar plate, and controls the dimensional accuracy of the bipolar plate.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: (1) Preparation of soft-cut carbon fiber foam: Cutting the three-dimensional soft-cut carbon fiber foam into the size of bipolar plates; (2) preparing a liquid resin: dissolving a solid resin in acetone at a mass ratio of 1:4, wherein the solid resin is any one of a vinyl ester resin, a compounded epoxy resin, and a polysulfone resin; (3) Preparing soft cut carbon fiber foam resin: immersing the soft cut carbon fiber foam described in step (1) in the liquid resin described in step (2) for 10 to 30 minutes, and drying in a vacuum drying oven at 25 to 40°C; (4) Pre-cold-pressing expanded graphite at 10-15 MPa as the top and bottom layers of the bipolar plate, wherein the mass fractions of the expanded graphite in the top and bottom layers of the bipolar plate are equal; (5) First, place the bottom layer of the bipolar plate described in step (4) into the mold, then place the soft cut carbon fiber foam resin described in step (3) in the middle layer, and finally place the top layer of the bipolar plate described in step (4) into the mold, heat to 90-150° C. under a pressure of 10-15 MPa and maintain for 110 seconds to 58 minutes. After the temperature cools down, demould to obtain a fuel cell composite bipolar plate.

[0007] Furthermore, the soft cut carbon fiber foam of the present invention accounts for 15-45% of the total mass fraction of the bipolar plate.

[0008] Furthermore, the mass fraction ratio of the soft cut carbon fiber foam to the liquid resin of the present invention is 1:1.

[0009] Furthermore, the expanded graphite of the present invention is one or a combination of flake graphite powder and graphite flakes.

[0010] Beneficial effects of the present invention: The soft cut carbon fiber foam used in the present invention has a rough surface and a uniform three-dimensional void network, which can effectively absorb liquid resin. The soft cut carbon fiber foam becomes short fibers and liquid resin (liquid resin is obtained by dissolving solid resin with a viscosity of 9000cps in acetone at a mass ratio of 1:4) under pressure. The rapid solidification shortens the solidification time, improves the dimensional accuracy and production efficiency of the bipolar plate, and coordinates the electrical conductivity, bending strength and air tightness. The "sandwich-type" sandwich structure of the present invention uses pre-cold-pressed expanded graphite at 10-15Mpa as the top layer and bottom layer of the bipolar plate to improve the electrical and thermal conductivity of the bipolar plate. The hot pressing molding preparation method of the present invention is simple and has high production efficiency. The prepared composite bipolar plate has a planar conductivity of 375.8S / cm, a maximum bending pressure of 88.53N, a bending strength of 61Mpa, and an air tightness of 2.32×10 - 8 cm 3 cm 2 s -1 , water contact angle is 92°, corrosion resistance current is 0.345μA / cm 2 , and can achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is an electron microscope structure diagram of the soft cut carbon fiber foam of the present invention; Figure 2 The electron microscope structure diagram of the soft cut carbon fiber foam resin of the present invention; Figure 3 This is a cross-sectional electron microscope structure diagram of the composite bipolar plate prepared in Example 1 of the present invention; Figure 4 This is a physical picture of the soft cut carbon fiber foam of the present invention; Figure 5 A physical picture of the solid vinyl ester used in the present invention; Figure 6 The composite bipolar plate prepared in Example 1 of the present invention; Figure 7 The composite bipolar plate prepared in Comparative Example 1; Figure 8 The composite bipolar plate prepared in Comparative Example 2; Fig. 9 The composite bipolar plate prepared in Comparative Example 4; Fig.10 This is the composite bipolar plate with flow channels prepared in Example 7 of the present invention. DETAILED DESCRIPTION

[0012] The present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples within the scope of the present invention. Example 1

[0013] A method for preparing a fast-curing expanded graphite-based fuel cell composite bipolar plate comprises the following steps: (1) Preparation of soft cut carbon fiber foam: Figure 1 The three-dimensional soft-cut carbon fiber foam of model VU-DJZ-3.5 (purchased from Hangzhou Weiken New Material Technology Co., Ltd.) is cut into bipolar plates with a size of 6.5×7 cm and a mass of 3 g; (2) Preparation of liquid resin: Figure 5 3 g of the solid vinyl ester resin shown was dissolved in 15 ml of acetone, allowed to stand for 5 min and then stirred for 5 min to completely dissolve the solid resin; (3) Preparation of soft cut carbon fiber foam resin: immerse 3 g of the soft cut carbon fiber foam described in step (1) into 3 g of the liquid resin described in step (2), let it stand for 10 min, and dry it in a vacuum drying oven at 40° C. for 2 hours to obtain a soft cut carbon fiber foam resin such as Figure 2 As shown; (4) Weigh 1.5 g of expanded graphite and pre-cold-press them at 10 MPa to form a top bipolar plate and a bottom bipolar plate; (5) First, place the bottom layer of the bipolar plate described in step (4) into the mold, then place the soft cut carbon fiber foam resin described in step (3) in the middle layer, and finally place the top layer of the bipolar plate described in step (4) into the mold, heat to 150°C under a pressure of 15 MPa, maintain for 110 seconds, and after cooling, demold to obtain a fuel cell composite bipolar plate with a thickness of 1.39 mm. Figure 3 , Figure 6 As shown, the smooth surface of the composite bipolar plate is conducive to surface hydrophobicity and is also convenient for subsequent processing.

[0014] Example 2 The other preparation methods are the same as those of Example 1, except that in step (5), the plate is heated to 90° C. under a pressure of 10 MPa and maintained for 58 minutes. After cooling, the plate is demoulded to obtain a fuel cell composite bipolar plate with a thickness of 1.44 mm. Example 3

[0015] A method for preparing a fast-curing expanded graphite-based fuel cell composite bipolar plate comprises the following steps: (1) Preparation of soft cut carbon fiber foam: Figure 4 The soft cut carbon fiber foam with three-dimensional structure shown is cut into bipolar plates with a size of 6.5×7 cm and a mass of 3 g; (2) Preparation of liquid resin: Dissolve 3 g of commercially available solid epoxy resin of model MERICAN 3300 (produced by Huachang Polymer Co., Ltd. of East China University of Science and Technology) in 15 ml of acetone, let stand for 5 min, and then stir slowly with a glass rod for 5 min to completely dissolve the solid resin; (3) Preparing soft cut carbon fiber foam resin: immersing the soft cut carbon fiber foam described in step (1) in the liquid resin described in step (2), leaving the mixture to stand for 30 minutes, and drying the mixture in a vacuum drying oven at 25° C. for 2 hours to obtain a soft cut carbon fiber foam resin; (4) Weigh 1.5 g of expanded graphite and pre-cold-press them at 15 MPa to form a top bipolar plate and a bottom bipolar plate; (5) First, place the bottom layer of the bipolar plate described in step (4) into the mold, then place the soft cut carbon fiber foam resin described in step (3) in the middle layer, and finally place the top layer of the bipolar plate described in step (4) into the mold, heat to 120° C. under a pressure of 15 MPa, maintain for 2.5 minutes, and after the temperature cools down, demold to obtain a fuel cell composite bipolar plate with a thickness of 1.45 mm.

[0016] The other preparation methods of Example 4 are the same as those of Example 3, except that in step (5), the plate is heated to 100° C. under a pressure of 10 MPa and maintained for 58 minutes. After the temperature is cooled, the plate is demoulded to obtain a fuel cell composite bipolar plate with a thickness of 1.43 mm. Example 5

[0017] A method for preparing a fast-curing expanded graphite-based fuel cell composite bipolar plate comprises the following steps: (1) Preparation of soft-cut carbon fiber foam: Cut the three-dimensional soft-cut carbon fiber foam into bipolar plates with a size of 6.5×7 cm and a mass of 3 g; (2) Preparation of liquid resin: Dissolve 3 g of solid polysulfone resin in 15 ml of acetone, let stand for 5 min, and then stir slowly with a glass rod for 5 min to completely dissolve the solid resin; (3) Preparing soft cut carbon fiber foam resin: immersing the soft cut carbon fiber foam described in step (1) in the liquid resin described in step (2), leaving the mixture to stand for 20 minutes, and drying the mixture in a vacuum drying oven at 32° C. for 2 hours to obtain soft cut carbon fiber foam@resin; (4) Weigh 1.5 g of expanded graphite and pre-cold-press them at 12 MPa to form a top bipolar plate and a bottom bipolar plate; (5) First, place the bottom layer of the bipolar plate described in step (4) into the mold, then place the soft cut carbon fiber foam resin described in step (3) on the middle layer, and finally place the top layer of the bipolar plate described in step (4) into the mold, heat to 130° C. under a pressure of 15 MPa, maintain for 4 minutes, and after the temperature cools down, demold to obtain a fuel cell composite bipolar plate with a thickness of 1.46 mm.

[0018] Example 6 The other preparation methods are the same as those of Example 5, except that in step (5), the plate is heated to 100° C. under a pressure of 15 MPa and maintained for 58 minutes. After cooling, the plate is demoulded to obtain a fuel cell composite bipolar plate with a thickness of 1.47 mm. Example 7

[0019] A method for preparing a fast-curing expanded graphite-based fuel cell composite bipolar plate comprises the following steps: (1) Preparation of soft-cut carbon fiber foam: Cut the three-dimensional soft-cut carbon fiber foam into bipolar plates with a size of 6.5×7 cm and a mass of 3.5 g; (2) Preparation of liquid resin: Dissolve 3.5 g of solid vinyl ester resin in 17.5 ml of acetone, let stand for 5 min, and then stir slowly with a glass rod for 5 min to completely dissolve the solid resin; (3) Preparing soft cut carbon fiber foam resin: immersing the soft cut carbon fiber foam described in step (1) in the liquid resin described in step (2), leaving the mixture to stand for 10 minutes, and drying the mixture in a vacuum drying oven at 40° C. for 2 hours to obtain a soft cut carbon fiber foam resin; (4) Weigh 1.5 g of expanded graphite and pre-cold-press them at 10 MPa to form a top bipolar plate and a bottom bipolar plate; (5) First, place the bottom layer of the bipolar plate described in step (4) into the mold, then place the soft cut carbon fiber foam resin described in step (3) in the middle layer, and finally place the top layer of the bipolar plate described in step (4) into the mold, heat to 140°C under a pressure of 15 MPa, maintain for 2 minutes and 30 seconds, and after the temperature cools down, demould to obtain the following Fig.10 Fuel cell composite bipolar plate shown with a thickness of 1.45 mm. Comparative Example 1

[0020] A method for preparing a fuel cell composite bipolar plate comprises the following steps: (1) Take 3g of expanded graphite and put it into a 6.5cm×7cm mold, and use a pressure of 15Mpa to cold press it once to obtain a pure expanded graphite sheet; (2) Take 3 g of solid vinyl ester resin in a beaker and add 15 ml of acetone in a mass ratio of 1:4. Let it stand for 5 min and then stir it slowly with a glass rod for 5 min to completely dissolve the solid resin in the acetone.

[0021] (3) Place the expanded graphite from step (1) in a culture dish, pour the liquid resin from step (2) into the culture dish, place the dish in a vacuum drying oven set to 40°C, evacuate for 5 minutes, and then keep it for 2 hours.

[0022] (4) Then, the temperature of the vacuum drying oven in step (3) was raised to 150° C. and maintained for 110 seconds. After the temperature was cooled, the plate was taken out to obtain a composite bipolar plate containing a fast-curing resin having a thickness of 1.23 mm, such as Figure 7 The surface of the composite sheet shown is rough, and the resin is impregnated in the surface layer of the expanded graphite, which will cause its electrical conductivity to be greatly reduced and its brittleness to be unfavorable for subsequent processing. Comparative Example 2

[0023] A method for preparing a fuel cell composite bipolar plate comprises the following steps: (1) Cut commercially available melamine foam with a thickness of 1.5 mm into pieces of 6.5 × 7 cm.

[0024] (2) Take 3 g of fast-curing solid vinyl ester resin in a beaker, take 15.0 ml of acetone in a mass ratio of 1:4 in the beaker, let it stand for 5 minutes, and then stir it slowly with a glass rod for 5 minutes to make the solid resin completely dissolved in the acetone.

[0025] (3) The melamine foam prepared in step (1) is placed in a culture dish, and the liquid resin prepared in step (2) is poured into the culture dish. The mixture is allowed to stand for 10 minutes to be completely absorbed by the melamine foam, and then the mixture is placed in a vacuum drying oven and dried at 40° C. for 2 hours.

[0026] (4) Pre-cold-press two portions of 1.5 g expanded graphite at 10 MPa as the top and bottom layers of the bipolar plate; (5) First, place the bottom layer of the bipolar plate described in step (4) into the mold, then place the soft cut carbon fiber foam resin described in step (3) in the middle layer, and finally place the top layer of the bipolar plate described in step (4) into the mold, heat to 150°C under a pressure of 15 MPa, maintain for 110 seconds, and after cooling, demold to obtain a fuel cell composite bipolar plate with a thickness of 1.35 mm. Figure 8 As shown, the surface is relatively rough, which is not conducive to surface hydrophobicity and subsequent processing. Comparative Example 3

[0027] A method for preparing a fuel cell composite bipolar plate comprises the following steps: (1) Preparation of soft-cut carbon fiber foam: Cut the three-dimensional soft-cut carbon fiber foam into bipolar plates with a size of 6.5×7 cm and a mass of 3 g; (2) Preparation of resin: Add 1.5 g of curing agent 4,4′-diaminodiphenyl sulfone to 3 g of liquid epoxy impregnation resin (AG-80 quaternary functional epoxy resin, purchased from Shanghai Huayi Resin Co., Ltd.), mix and stir for 10 min; (3) preparing a soft cut carbon fiber foam resin: immersing the soft cut carbon fiber foam described in step (1) in the epoxy impregnation resin described in step (2) and allowing to stand for 10 minutes, and drying in a vacuum drying oven at 40° C. for 2 hours to obtain a soft cut carbon fiber foam resin; (4) Pre-cold-press two portions of 1.5 g expanded graphite at 10 MPa as the top and bottom layers of the bipolar plate; (5) First, place the bottom layer of expanded graphite that has been pre-cold pressed in step (4) into the mold, then place the soft cut carbon fiber foam resin in step (3) in the middle layer, and finally place the top layer of expanded graphite that has been pre-cold pressed in step (4) into the mold, heat to 150° C. at a pressure of 15 MPa, maintain for 2 hours, and after the temperature cools down, demold to obtain a fuel cell composite bipolar plate with a thickness of 1.52 mm. Comparative Example 4

[0028] A method for preparing a fuel cell composite bipolar plate comprises the following steps: The other preparation methods are the same as those in Example 1, except that the expanded graphite as the top and bottom layers of the bipolar plate is not subjected to the pre-cold pressing treatment in step (4) to obtain a fuel cell composite bipolar plate with a thickness of 1.48 mm. Fig. 9 As shown, the surface is rough and the expanded graphite cannot be completely arranged on the surface of the plate, resulting in stratification, which is not conducive to hydrophobicity and subsequent processing.

[0029] The performance test results of the composite bipolar plates obtained in the above Examples 1-7 and Comparative Examples 1-4 are shown in Table 1: (1) Bending strength test of bipolar plates: The bending strength of bipolar plates was tested using an electronic universal testing machine (Shimadzu, 33012) and a three-point bending method. The span of the test sample used in this test was 32 times the thickness to improve accuracy. The samples for the bending strength test were uniformly 60 mm in length, 10 mm in width, and 1.2-1.5 mm in thickness. The test speed was 2 mm / s and the lower span was 45 mm. (2) The area specific resistance is tested according to GB / T20042.6. The support layer is made of carbon paper used for the diffusion layer of fuel cells; the electrode is a metal-plated electrode, generally a gold-plated electrode; (3) The electrical conductivity was tested using a four-probe resistivity tester (Keithley, 2400); (4) Gas permeability is tested using a gas leak detector (AIRTEK, N50); (5) The surface roughness is tested by an optical 3D surface profiler (WX-S100).

[0030] (6) Water contact angle measuring instrument (JC2000DS2B, Shanghai Zhongchen Digital Technology Equipment Co., Ltd.) test; Corrosion resistance test: (7) The electrochemical performance of the composite board was tested using an electrochemical workstation (Shanghai Chenhua CHI660E). A three-electrode system was used to test the electrochemical performance of the composite board. 2The sample is the working electrode, the calomel electrode is the reference electrode, and the platinum sheet is the counter electrode. The experiment uses 0.5 MH2SO4 as the electrolyte, at 80°C, with a scanning rate of 2 mV / s, and a Tafel curve test is performed to measure the corrosion current of the composite bipolar plate.

[0031] (8) Dimensional deviation is tested using a vernier caliper (Shanghai Measuring Tool and Cutting Tool Factory Co., Ltd. ISO9001).

[0032] Table 1 Performance test table of composite bipolar plates of Examples 1-7 and Comparative Examples 1-4

[0033]

[0034] As can be seen from Table 1, Comparative Example 1 is expanded graphite impregnated with a fast-curing resin, lacking soft-cut carbon fiber foam as an intermediate medium. The bending strength, area specific resistance, corrosion resistance and gas permeability of the composite bipolar plate after impregnation cannot meet the application requirements (bending strength greater than 25 MPa, area specific resistance less than 10 mΩ·cm 2 , gas permeability is less than 2.0×10-6cm 3 cm -2 s -1 , corrosion current is less than 1μA / cm 2 ), Comparative Example 2 is an expanded graphite-melamine foam fast curing resin composite bipolar plate, using melamine foam instead of soft cut carbon fiber foam as the intermediate medium, so that the resin can exist in the middle layer, and the sandwich composite bipolar plate is designed with a "sandwich" structure. Although the conductivity and air tightness are improved to a certain extent, the bending strength is greatly reduced. In Comparative Example 3, the polymer is a liquid resin in the prior art, which requires a long curing time. The difference in polymers leads to a difference in bipolar plate performance. Although its overall performance meets the requirements of the application, it still has a certain gap compared with Example 1. Comparative Example 4 is different from Example 1 in that the expanded graphite on the surface layer of the bipolar plate is not pre-cold pressed. Although both meet the requirements of the application, its overall performance is not as good as Example 1. The present invention uses soft cut carbon fiber foam and fast curing resin as an intermediate medium, which not only improves the conductivity of the bipolar plate, but also meets the requirements of its bending strength, improves air tightness and corrosion resistance, uses expanded graphite as the outer layer to effectively improve the conductivity of the bipolar plate, and uses high temperature fast curing epoxy resin as a polymer to improve the production efficiency of the bipolar plate, and effectively controls the dimensional accuracy, which can be mass-produced industrially. The design of the "sandwich" type interlayer structure not only has good hydrophobicity and corrosion resistance, but also can balance the requirements of the conductivity, bending strength and air tightness of the bipolar plate. The preparation process of the present invention is simple, and the prepared composite bipolar plate has excellent comprehensive performance.

[0035] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a fast-curing expanded graphite-based fuel cell composite bipolar plate, characterized in that: The steps include: (1) Preparation of soft-cut carbon fiber foam: Cutting the three-dimensional soft-cut carbon fiber foam into the size of bipolar plates; (2) preparing a liquid resin: dissolving a solid resin in acetone at a mass ratio of 1:4, wherein the solid resin is any one of a vinyl ester resin, a compounded epoxy resin, and a polysulfone resin; (3) Preparing soft cut carbon fiber foam resin: immersing the soft cut carbon fiber foam described in step (1) in the liquid resin described in step (2) for 10 to 30 minutes, and drying in a vacuum drying oven at 25 to 40°C; (4) Pre-cold-pressing expanded graphite at 10-15 MPa as the top and bottom layers of the bipolar plate, wherein the mass fractions of the expanded graphite in the top and bottom layers of the bipolar plate are equal; (5) First, place the bottom layer of the bipolar plate described in step (4) into the mold, then place the soft cut carbon fiber foam resin described in step (3) in the middle layer, and finally place the top layer of the bipolar plate described in step (4) into the mold, heat to 90-150° C. under a pressure of 10-15 MPa and maintain for 110 seconds to 58 minutes. After the temperature cools down, demould to obtain a fuel cell composite bipolar plate.

2. The method for preparing a fast-curing expanded graphite-based fuel cell composite bipolar plate according to claim 1, characterized in that: The soft-cut carbon fiber foam in step (1) accounts for 15-45% of the total mass of the bipolar plate.

3. The method for preparing a fast-curing expanded graphite-based fuel cell composite bipolar plate according to claim 1, characterized in that: In step (3), the mass ratio of the soft cut carbon fiber foam to the liquid resin is 1:

1.

4. A method for preparing a fast-curing expanded graphite-based fuel cell composite bipolar plate according to any one of claims 1 to 3, characterized in that: The expanded graphite in step (4) is one or a combination of flake graphite powder and graphite flakes.

Citation Information

Patent Citations

  • Expansion graphite base compound material dual-pole board and its making method

    CN101101994A

  • Bipolar plate for vanadium battery and preparation method of bipolar plate

    CN104466197A

  • Layered composite graphite polar plate for fuel cell and preparation method of layered composite graphite polar plate

    CN114976097A

  • High-performance flexible graphite bipolar plate and preparation method thereof

    CN117613295A

  • Manufacturing method of ultrathin graphite bipolar plate for fuel cell

    CN118712406A

Cited By

  • Graphite-based fuel cell composite bipolar plate and preparation method thereof

    CN121215797A

  • A fuel cell composite bipolar plate based on liquid metal anchoring and electrochemical deposition and a method for manufacturing the same

    CN122800643A